PC based SMPS protection - Mohd Shakirun Naim, Md Isa (2008)
The PC Based SMPS Protection is a system that preventing the electrical equipment from damage due to overvoltage and overcurrent. This project is able to replace the function of fuse, increase efficiency of protection and reduce maintenance cost. This project basically focus on the designing the system include sensing elements, amplifier circuit and software (VB.net). When overvoltage or overcurent occurred the system is automatically turn-off the supply to the load by disable the PWM signal to the SMPS. In addition, the warning message is activated due to this problem to alerts the user from the problem occurred. Thus, the load or electrical components are safe from damage of overvoltage and overcurrent. The system detects the overvoltage and overcurrent from sensing circuit that using the shunt resistor concepts. The system used DAQ (USB-4716) as the data acquisition to convert the analogue to digital data (ADC) for data logging and integrated with the VB.net programming language to communicate with user. Through PC, user can monitor the status of the current and voltage to the load or electrical components.